A Contrastive Analysis Of Passive and Active Voice In Indonesian and English - Rimelni Sidabutar; Lonatasya Nainggolan; Aulia Agustina; Anita Sitanggang (CV Putra Publisher, 2023)
This research paper presents a contrastive analysis of passive and active sentences in Indonesian and English. The research aims to uncover the similarities, differences, and patterns underlying the use of these grammatical features in both languages. This research utilizes descriptive qualitative research. This paper explores the different forms and patterns of active and passive sentences in Indonesian and English through the analysis of spoof texts. The data analysis shows that the most dominant form of active sentences in English is the past tense (63.6%), while in Indonesian, the transitive form is the most widely used (66.7%). This contrastive analysis provides valuable insights into the linguistic structures and communicative strategies used by Indonesian and English speakers,contributing to language learning and understanding cross-linguistic differences.